2011
DOI: 10.14710/jitaa.36.1.61-68
|View full text |Cite
|
Sign up to set email alerts
|

EGG QUALITY AND HATCHABILITY OF In situ - REARED KEDU AND CEMANI HENS FED DIET OF FARMER FORMULATION SUPPLEMENTED WITH VITAMIN E

Abstract: The aim of study was to evaluate the effect of dietary vitamin E supplementation in Kedu and Cemani hens reraed in situ and given farmer-formulated diet on egg performances. A total of 120 female and 24 male birds were equally divided into two groups of Kedu and Cemani, with average body weight of 1890+216.79 and 1830+396.23 g, respectively. Basal ration was based on the diet formulated by the farmer (R1) consisting of corn (30%), rice bran (50%), protein concentrate (15%), and premix (5%).Dietary treatments e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
2
3
0
1
Order By: Relevance
“…These results agree also with those of Wahyuni et al (2011) who showed that vitamin E supplementation did not affect feed consumption in Kedu and Cemani hens. Krishnan and Scheideler (2010) showed that dietary supplementation with choline (choline chloride 60%) at 0, 500 and 1000 ppm did not show any difference in feed intake in 29-week-old White Leghorn hens.…”
Section: Productive Performance Of Turkey Henssupporting
confidence: 93%
“…These results agree also with those of Wahyuni et al (2011) who showed that vitamin E supplementation did not affect feed consumption in Kedu and Cemani hens. Krishnan and Scheideler (2010) showed that dietary supplementation with choline (choline chloride 60%) at 0, 500 and 1000 ppm did not show any difference in feed intake in 29-week-old White Leghorn hens.…”
Section: Productive Performance Of Turkey Henssupporting
confidence: 93%
“…In order to ensure the chickens are able to grow as good breeder flock, the feed should be sufficient in nutrients supply, especially in relation to egg fertility. As reported by Wahyuni et al (2011) that addition of vitamin E up to 6 IU to Kedu hens showed a linear pattern. Kedu hens receiving vitamin E have improved their fertility and hatchability by 7 to 10% and 2 to 8%, respectively.…”
Section: Introductionsupporting
confidence: 53%
“…Some previous studies have been done concerning dietary addition of vitamin E, in Indonesian local chicken (Nataamijaya, et al, 2006;Iriyanti et. al., 2007;Wahyuni, et. al., 2011); Taiwan local chicken (Lin et.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan data pada Gambar 1 didapatkan bahwa pemberian ekstrak sarang semut dapat meningkatkan fertilitas telur ayam. Vitamin E memiliki peranan yang sangat penting dalam reproduksi ternak (Wahyuni et al, 2011;Iriyanti dkk.,, 2007). Peningkatan fertilitas ditentukan juga oleh pakan yang cukup mengandung vitamin E. Pada durasi pemberian 3 hari/minggu (D3), level pemberian ekstrak umbi sarang semut sebesar 10 mg/kg BB (L1) menghasilkan fertilitas yang lebih rendah dibanding level pemberian ekstrak umbi sarang semut sebesar 20 mg/kg BB (L2).…”
Section: Hasil Dan Pembahasanunclassified